Electroconvulsive Therapy and Risk of Dementia—A Nationwide Cohort Study in Taiwan - Chu, Ching-Wen; Chien, Wu-Chien; Chung, Chi-Hsiang; Chao, Pei-Chun; Chang, Hsin-An; Kao, Yu-Chen; Chou, Yu-Ching; Tzeng, Nian-Sheng (Frontiers in Psychiatry, 2018)
Background: Electroconvulsive therapy (ECT) is an effective treatment for schizophrenia, bipolar disorder, and major depressive disorder, and a temporary memory loss may occur after ECT. However, the association between ECT in patients with schizophrenia, bipolar disorder, and major depressive disorder, and the risk of dementia is yet to be examined. Objective: This study aimed to clarify as to whether ECT is associated with the risk of dementia after ECT in patients with schizophrenia, bipolar disorder, and major depressive disorder, using Taiwan's National Health Insurance Research Database (NHIRD). Methods: A total of 3,796 enrolled participants (schizophrenia, 46.68%; bipolar disorder, 11.77%; and major depressive disorder, 41.55%) with 994 patients who had received ECT and 2,982 controls matched for sex and age, between January 1, and December 31, 2000, were selected from the NHIRD. After adjusting for confounding factors, Fine and Gray's survival analysis was used to compare the risk of developing dementia during the 10 years of follow-up. Results: Of the study patients, 45 (4.53%) of them developed dementia when compared to 149 (5.0%) in the control group. Fine and Gray's survival analysis revealed that the study patients were not associated with an increased risk of dementia [hazard ratio (HR) = 0.612, 95% confidence interval (CI) = 0.438–1.854, P = 0.325]. After adjusting for sex, age, monthly income, urbanization level, geographic region, and comorbidities, the adjusted HR was 0.633 (95% CI = 0.448 – 1.895, P = 0.304). Conclusion: This study supports that ECT was not associated with the increased risk of dementia in patients with schizophrenia, bipolar disorder, and major depressive disorder, using the NHIRD.